Assessment of Waste Management Program Implementation in a Local Community: Penilaian Implementasi Program Pengelolaan Sampah di Sebuah Komunitas Lokal - Suwito, Atam Yudha; Sukmana, Hendra (Indonesian Journal of Law and Economics Review, 2024)
The general background this research focuses on the implementation of the Integrated Waste Management Program (TPST) to address waste management issues at the village level. Specific background includes the lack of understanding regarding the effectiveness of existing waste management programs, which often do not run optimally. Knowledge gap this drives further research to evaluate these programs. Aims of this research is to describe and analyze the implementation of the TPST waste management program and assess the indicators that influence its success. Results of the research show that the implementation of this program is considered quite good with the indicators of communication, resources, disposition, and bureaucratic structure having been met. Novelty of this research lies in the application of implementation theory by George Edward III in the context of waste management in villages, providing new insights into the factors that influence program effectiveness. Implications of this research suggest that village governments conduct ongoing evaluations and improvements to facilities and infrastructure to enhance the quality of waste management and produce organic fertilizer, thereby reducing the amount of residue generated. Highlights: Implementation assessed through indicators: communication, resources, disposition, and bureaucratic structure. Ongoing evaluations are essential for enhancing waste management effectiveness. Recommendations include improving facilities to produce organic fertilizer and reduce waste residue. Keywords: Waste Management, Integrated Program, Implementation, Community Engagement, Resource Allocation